2008
DOI: 10.1245/s10434-008-9884-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Diameter as a Prognostic Factor in Patients with Gastric Cancer

Abstract: Tumor diameter in gastric cancer is a reliable prognostic factor that might be a candidate for use in the staging system. To improve outcomes for patients with tumors >/=100 mm in diameter, it is necessary to establish therapeutic strategies for peritoneal metastasis, particularly in stage II and III tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 14 publications
3
29
0
Order By: Relevance
“…The results from our study also support the previously described finding that patient age at the time of diagnosis is significantly associated with overall survival in Western and Eastern GC patients [23,24]. Confirming previous reports [25][26][27], tumor size was also identified as a poor prognostic factor in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…The results from our study also support the previously described finding that patient age at the time of diagnosis is significantly associated with overall survival in Western and Eastern GC patients [23,24]. Confirming previous reports [25][26][27], tumor size was also identified as a poor prognostic factor in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Kunisaki et al [8] examined 1215 patients with gastric cancer and classified them into groups with smaller tumors and those with larger tumors, by setting 100 mm as the cutoff value for the maximal tumor diameter. They found that OS was markedly different between stage II/III patients with smaller and larger tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Gross appearance and size of the tumor has also been introduced as an indicator for deciding the extend of lymph node resection even in early stages of gastric cancer (Tsujitani et al, 1999) and leads to modification of curative and palliative interventions (Li et al, 2009). However results of these studies differ in regard of the proposed threshold of tumor size; ranging between 35 to 100mm and even up to 8cm (Kunisaki et al, 2008). This difference could be a result of histopathology of the tumor or may be influenced by other factors affecting the survival like treatment methods.…”
Section: Discussionmentioning
confidence: 96%
“…This difference could be a result of histopathology of the tumor or may be influenced by other factors affecting the survival like treatment methods. Further researches are needed to make a conclusion before performing recommendation of researchers to include the tumor size in staging system of gastric cancer (Kunisaki et al, 2008;Wang et al, 2008;Liu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%